Using Graphene Oxide High Near-Infrared Absorbance for Photothermal Treatment of Alzheimer's Disease - Li, Meng; Yang, Xinjian; Ren, Jinsong; Qu, Konggang; Qu, Xiaogang (Advanced materials (Weinheim), 2012)
A novel strategy to dissociate amyloid aggregation is presented, using localised heat generation from a clinically used amyloid staining dye, thioflavin‐S (ThS)‐modified graphene oxide (GO) under NIR laser irradiation. Compared to traditional chemotherapies, photothermal therapy shows reduced side effects and improved selectivity and safety.